2012
DOI: 10.1002/path.3969
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response is associated with early tau pathology in the hippocampus of tauopathies

Abstract: The unfolded protein response (UPR) is a stress response activated upon disturbed homeostasis in the endoplasmic reticulum (ER). Previously, we reported that the activation of the UPR closely correlates with the presence of phosphorylated tau (p-tau) in Alzheimer's disease (AD). As well as increased presence of intracellular p-tau, AD brains are characterized by extracellular deposits of β amyloid (Aβ). Recent in vitro studies have shown that Aβ can induce ER stress and activation of the UPR. The aim of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(170 citation statements)
references
References 29 publications
(38 reference statements)
17
149
4
Order By: Relevance
“…Melatonin suppressed the upregulation of CHOP and caspase -12 induced by METH. Increased expression of CHOP triggers the ER stress-induced cell death that is mostly found in various neurodegenerative diseases such as ischemia and Alzheimer's disease (Lindholm et al, 2006;Doyle et al, 2011;Larner et al, 2006;Nijholt et al, 2012). This result suggested that melatonin improves ER function, thereby suppressing ER stress-induced cell death.…”
Section: Discussionmentioning
confidence: 91%
“…Melatonin suppressed the upregulation of CHOP and caspase -12 induced by METH. Increased expression of CHOP triggers the ER stress-induced cell death that is mostly found in various neurodegenerative diseases such as ischemia and Alzheimer's disease (Lindholm et al, 2006;Doyle et al, 2011;Larner et al, 2006;Nijholt et al, 2012). This result suggested that melatonin improves ER function, thereby suppressing ER stress-induced cell death.…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, increased levels of p-eIF2α were found in the cortex and hippocampus of AD patients and in AD mouse models (Chang et al, 2002b; Devi and Ohno, 2013; Hoozemans et al, 2009; Kim et al, 2007; Lewerenz and Maher, 2009; Ma et al, 2013; Mouton-Liger et al, 2012; O’Connor et al, 2008; Page et al, 2006; Stutzbach et al, 2013; Unterberger et al, 2006). In addition to AD, p-eIF2α levels are elevated in the brain or spinal cord of patients and mice with prion disease (Unterberger et al, 2006), amyotrophic lateral sclerosis (ALS; Ilieva et al, 2007), Parkinson’s disease (PD; Hoozemans et al, 2007, 2012), Huntington’s disease (HD; Leitman et al, 2014), and various tauopathies (Köhler et al, 2014; Nijholt et al, 2012; Radford et al, 2015; Stutzbach et al, 2013; Unterberger et al, 2006). …”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 99%
“…13 Accumulating evidences show that ER stress induces tau phosphorylation (Ho et al, 2012), as well, reduces amyloid β peptide secretion (Suga K et al, 2015) and finally causes Aβ accumulation (Liu et al, 2012). Conversely, abnormal tau phosphorylation and Aβ deposit activate ER stress and mitochondria apoptosis pathway to cause neuronal death in the neurodegenerative process (Costa et al, 2013;Ho et al, 2012;Nijholt et al, 2012;Pinkaew et al, 2015). This positive loop may play an important role in the development of AD.…”
Section: Discussionmentioning
confidence: 99%